2004
DOI: 10.1124/jpet.104.068171
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivation of 1,1-Dichloroethylene by CYP2E1 and CYP2F2 in Murine Lung

Abstract: 1,1-Dichloroethylene (DCE) exposure evokes lung toxicity with selective damage to bronchiolar Clara cells. Recent in vitro studies have implicated CYP2E1 and CYP2F2 in the bioactivation of DCE to 2-S-glutathionyl acetate [C], a putative conjugate of DCE epoxide with glutathione. An objective of this study was to test the hypothesis that bioactivation of DCE is catalyzed by both CYP2E1 and CYP2F2 in murine lung. Western blot analysis of lung microsomal proteins from DCE-treated CD-1 mice showed time-dependent l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 22 publications
5
40
1
Order By: Relevance
“…Cell extracts for metabolite detection were prepared by suspension of frozen (Ϫ70°C) cell pellets containing ϳ1,600 g of protein in 500 l of water, followed by sonication to disrupt cells and then filtration through 0.2-m cellulose membrane filters (Spartan 13; Whatman). An HPLC-MS method was developed for detection of GSH based on a method described by Simmonds et al (55). Metabolites were separated with an Agilent series 1100 HPLC equipped with a Supelcosil LC-8 guard column and an Intersil ODS-3 column (C 18 ; 250 nm by 4.6 nm; particle size, 5 m).…”
Section: Methodsmentioning
confidence: 99%
“…Cell extracts for metabolite detection were prepared by suspension of frozen (Ϫ70°C) cell pellets containing ϳ1,600 g of protein in 500 l of water, followed by sonication to disrupt cells and then filtration through 0.2-m cellulose membrane filters (Spartan 13; Whatman). An HPLC-MS method was developed for detection of GSH based on a method described by Simmonds et al (55). Metabolites were separated with an Agilent series 1100 HPLC equipped with a Supelcosil LC-8 guard column and an Intersil ODS-3 column (C 18 ; 250 nm by 4.6 nm; particle size, 5 m).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, is naphthaleneinduced cytotoxicity in the rat and mouse nose the result of CYP2F2 metabolism or metabolism by another CYP? 2� If there is mild naphthalene-induced injury in rat alveolar epithelial cells (and so far the data do not strongly Although Phimister et al� (2004) showed that naphthalene inhalation causes GSH depletion in the mouse respiratory tract, which is correlated with an increase in naphthalene protein adduct formation in mouse airway, and an increase in cellular injury and toxicity at the same site, this study did not specifically examine whether CYP2F naphthalene bioactivation was correlated with GSH depletion� This study, in combination with the naphthalene metabolism studies discussed earlier, is fairly supportive that CYP2F activity is likely involved, at least in part, in the formation of naphthalene metabolites responsible for naphthalene-induced GSH depletion and mouse lung cytotoxicity� However, as discussed above, the potential for involvement of CYP2E1 cannot be ruled out, and a recent study (Simmonds et al�, 2004) showed that both CYP2F2 and CYP2E1 are involved in 1,1-DCE bioactivation and lung toxicity in mice� In addition, naphthalene (but not 1-naphthol) cytotoxicity in human MNLs was increased in the presence of CYP2E1-induced rat liver microsomes (Wilson et al�, 1996), suggesting that CYP2E1 may be involved in formation of the epoxide but that another CYP may be involved in further metabolism of the 1-naphthol to the quinones� Therefore, as shown in Table 3, the mouse lung data provide "some evidence" that CYP2F is involved in cytotoxicity in the mouse lung, since the data currently cannot rule out the involvement of other CYPs�…”
Section: Since the Cyp2f Inhibitor (5-pip) Also Inhibits Cyp2e1 Coulmentioning
confidence: 91%
“…Wild-type mice treated (IP injection) with naphthalene and a CYP2F inhibitor (5-PIP) showed no signs of lung or olfactory toxicity, as compared to the mice treated with naphthalene and no inhibitor where toxicity was observed in lung (hemorrhagic lungs) and olfactory tissue (100% sloughing of olfactory mucosa) (Genter et al�, 2006)� This study has been frequently cited in the literature as support that CYP2F is the CYP involved in metabolic activation of naphthalene to its toxic metabolites in mouse lung� Although these studies are supportive, especially in combination with the immunolocalization studies correlating CYP2F with the naphthalene epoxide at the site of injury in mouse lung, it is important to consider that the CYP2F inhibitor (5-PIP) also inhibits CYP2E1, which is also present in mouse lung and rat nose� Therefore, one needs to consider the possibility that CYP2E1 could be involved in naphthalene metabolism� However, the relative activities of these enzymes toward naphthalene needs consideration� Recombinant CYP2F from mice and rats efficiently generates the naphthalene oxide: CYP2F4 from rats (K M = 3 µM, V max = 107 min −1 ) (Baldwin et al�, 2005); and CYP2F2 from mice (K M = 3 µM, V max = 104 min −1 ) (Shultz et al�, 1999)� We did not find any studies that evaluated the activity of rodent CYP2E1 toward naphthalene� However, recombinant CYP2E1 from humans metabolized naphthalene to its 1-naphthol metabolite at a much lower efficiency (K M = 10�1 µM, V max = 8�4 min −1 ) (Cho et al�, 2006)� These data suggest that CYP2F metabolizes naphthalene more efficiently than CYP2E1, but studies comparing both CYPs in humans and rodents would provide stronger evidence as to the relevance of these two CYPs in various species� Studies in CYP2E1 and CYP2F knockout mice, or with inhibitors specific to CYP2E1, would provide useful information in this regard� Accordingly, as shown in Table 3, the mouse lung data provide "some evidence" that CYP2F is the primary CYP involved in metabolism of naphthalene to the epoxide, but more studies are necessary before we can rule out the involvement of CYP2E1 in metabolic activation of naphthalene to its toxic metabolites in mouse lung� CYP2E1 is present in mouse nasal and lung tissues (Simmonds et al�, 2004;Green et al�, 2001)� One possibility might be that CYP2E1 and CY2F2 are both involved in metabolic activation of naphthalene and cytotoxicity� There is some precedent for considering this possibility; a recent study of 1,1-DCE bioactivation and cytotoxicity in murine Clara cells (Simmonds et al�, 2004) suggested that both CYP2F2 and CYP2E1 are involved in 1,1-dichloroethylene (1,1-DCE) bioactivation and lung toxicity� Immunolocalization studies indicated that the rat nasal mucosa (primarily the olfactory epithelium) contains high levels of CYP2F4 (Baldwin et al�, 2004)� In addition, a recent study by Morris and Buckpitt (2009) found that naphthalene metabolism in the rat nose was inhibited after pretreatment with 5-PIP, suggesting that CYP2F is likely responsible, at least in part, for naphthalene metabolism in the rat nose� Therefore, as shown in Table 3, the rat nasal data provide "some evidence" that CYP2F4 is responsible for naphthalene metabo...…”
Section: Since the Cyp2f Inhibitor (5-pip) Also Inhibits Cyp2e1 Coulmentioning
confidence: 99%
“…Forkert (2001) and Simmonds et al (2004) conclude from studies of mouse liver and lung that DCE epoxide is the most important cytotoxic metabolite. Dowsley et al (1999) also find CYP2E1-mediated …”
Section: Discussionmentioning
confidence: 99%